2001
DOI: 10.1080/02652030117235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight distribution of carrageenans studied by a combined gel permeation/inductively coupled plasma (GPC/ICP) method

Abstract: Degraded carrageenan (known as poligeenan molecular weight: 20 kDa to 30 kDa) causes ulcerative colitis in experimental animals. In this paper, the molecular weight distributions of 29 samples of food-grade refined carrageenans were studied by high performance liquid gel permeation chromatography (GPC) directly connected to vacuum-ultraviolet inductively coupled plasma-atomic emission spectrometry (ICP) (GPC/ICP) as well as GPC/refractive index (RI) detection. All samples of food-grade carrageenan had a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Although the curves regionally overlap reasonably well we would not take that plot for an appropriate substitute of direct molar mass detection. This is not the place to make a statement on the validity of the principle of universal calibration, but in our own studies universal calibration has always been superior to the proposal made in Ref 45…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Although the curves regionally overlap reasonably well we would not take that plot for an appropriate substitute of direct molar mass detection. This is not the place to make a statement on the validity of the principle of universal calibration, but in our own studies universal calibration has always been superior to the proposal made in Ref 45…”
Section: Resultsmentioning
confidence: 52%
“…This is not the place to make a statement on the validity of the principle of universal calibration, but in our own studies universal calibration has always been superior to the proposal made in Ref. 45.…”
Section: Searching For Good Separation Conditions For Carrageenansmentioning
confidence: 52%
“…Interest in establishing a specification of the LMT of CGN originated in a 2003 opinion expressed by the European Commission's Scientific Committee on Food (SCF) (European Commission 2003). The SCF evaluated a 2001 paper by Uno et al (2001b). This research team reported that they analyzed more than two dozen samples of CGN and measured the weight average molecular weight at greater than 450,000 Da.…”
Section: Gel Formation No Gel Formation Functional Properties In Foodmentioning
confidence: 99%
“…Also, some cellular therapy related studies and ideas to use hydrocolloid ma-terial with prostheses can be found in the literature. [15][16][17][18] Candidates for replacing these gums are difficult to find. In analytics, the preparation of biopsy samples has been reported to become easier if glucomannan-based special fixation support agents are used.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are guar gum, gum arabic, carrageenan, and xanthan gum, all of which have high molar masses, possess good properties for modifying solution viscosities, and act as emulsifying agents. [15][16][17][18] Candidates for replacing these gums are difficult to find. A common denominator for these products is the requirement of high molar mass, as it is one of the key factors governing their beneficial properties.…”
Section: Introductionmentioning
confidence: 99%